Mechanisms of Aerobic Exercise Impairment in Diabetes: A Narrative Review - Wahl, Matthew P.; Scalzo, Rebecca L.; Regensteiner, Judith G.; Reusch, Jane E. B. (Frontiers in Endocrinology, 2018)
The prevalence of diabetes in the United States and globally has been rapidly increasing over the last several decades. There are now estimated to be 30.3 million people in the United States and 422 million people worldwide with diabetes. Diabetes is associated with a greatly increased risk of cardiovascular mortality, which is the leading cause of death in adults with diabetes. While exercise training is a cornerstone of diabetes treatment, people with diabetes have well described aerobic exercise impairments that may create an additional diabetes-specific barrier to adding regular exercise to their lifestyle. Physiologic mechanisms linked to exercise impairment in diabetes include insulin resistance, cardiac abnormalities, mitochondrial function and the ability of the body to supply oxygen. In this paper, we highlight the abnormalities of exercise in type 2 diabetes as well as potential therapeutic approaches.